Residents\' and Interns\' Knowledge about Nutrition in Shahid Beheshti University of Medical Sciences - Malek Alimohammadi Kamalabadi; Naser Kalantari; Narguess Abdous; Mehrassa Mohamadsadeghi (مجله ایرانی آموزش در علوم پزشکی, 2010)
Introduction: Considering the important role of nutrition in health, attaining a high nutritional knowledge is essential for physicians. So, this study was performed with the aim of determining the level of residents' and interns' knowledge about nutrition in Shahid Beheshti University of Medical Sciences and Health Services. Methods: Sixty six interns and 70 residents were selected randomly out of the total target population in this descriptive cross-sectional study and received the nutritional knowledge questionnaire in hospitals affiliated to the medical university. They all filled and returned the questionnaires before the end of official working hour. Data was analyzed by SPSS software using ANOVA, and chi². Results: The level of nutritional knowledge was weak in 25.3%, average in 61.3%, and good in 13.4% of the participants. But none of the participants had a very good level of nutritional knowledge. The mean score for correct answers was 50.28. Ninety three point seven percent of residents and interns had no idea about the relationship between overconsumption of Vitamin C in pregnancy and infant’s dependency to this Vitamin and 80.3% were also not aware of the relationship between overconsumption of Protein and Calcium excrete. Among the participants, 96.5% knew no comprehensive reference on nutrition and no one identified any website or journal in the field of nutrition. Conclusion: This study affirmed the results of preceding studies implicating the necessity of enhancing nutritional knowledge in medical universities' curriculum and during clinical activities.